Analysis of thyroid dysfunction in patients with sudden sensorineural hearing loss - Yuhua Zhu; Dan Bing; Dayong Wang; Lidong Zhao; Zifang Yin; Qiujing Zhang; Jing Guan; Qiuju Wang (World Journal of Otorhinolaryngology-Head and Neck Surgery, 2021)
Background: Sudden sensorineural hearing loss (SSHL) refers to the sudden occurrence of unexplained sensorineural hearing loss. The present study showed that different systemic diseases had different influence on the occurrence and hearing outcome of SSHL. Thyroid hormone is one of the important factors for the development of fetal ear and auditory function. However, the distribution of thyroid dysfunction in SSHL patients and the effect of thyroid dysfunction on the occurrence and hearing outcome of SSHL has not been studied. Methods: In this study, a retrospective analysis had been done in 676 patients with SSHL. We had described the distribution of thyroid function in patients with SSHL in detail, and by the statistical method, analyzed the relationship between the hearing outcome and thyroid dysfunction, respectively. Results: In all patients, 24.41% (165/676) had abnormal thyroid function testing results. The onset age of SSHL in FT3 abnormal group (including low and high group) was younger than that in normal FT3 group. Recovery group had more patients with lower-than-normal T3 level as compared to non-recovery patients. Significant associations between T3 levels and hearing outcome were observed in the subgroup with longer time elapse between symptom onset and treatment (≥14 d). Conclusion: The incidence of thyroid dysfunction in SSHL is significantly higher than in the general population. There was obvious relationship between T3 and FT3 item of thyroid dysfunction and the onset time and hearing outcome of SSHL, which indicated that T3 or FT3 indicator may be one of the affecting factors for the SSHL. Early screening and diagnosis of thyroid dysfunction, especial T3 level, may help to evaluate the prognosis in SSHL patients.